PERILAKU MEROKOK DAN KONTROL DIRI PADA SISWA MTSS MANBA’UL HUDA KALITEKUK KEC. GAJAH KAB. DEMAK - Kartubi, Kartubi; Adinda Prabowo Putri, Siska (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas AKI Semarang, 2025)
This study aims to empirically test the relationship between self-control and the tendency of smoking behavior in students at MTSS Manba'ul Huda Kalitekuk Kec. Gajah Kab. Demak. The sample criteria in this study were male and had tried smoking. The sampling technique used was purposive sampling. The number of samples used was 55 students. The analysis used was multinomial logistic regression. The variable of the tendency of smoking behavior was measured using a questionnaire based on the theory of four aspects of the tendency of smoking behavior, namely the function of smoking, smoking intensity, smoking time and smoking place. The measurement of the self-control variable, the researcher used the theory of self-control aspects from De Ridder, namely inhibition and initiation. The results of this study indicate that self-control affects the intensity of smoking in students and the age of onset of smoking, but on the contrary self-control does not affect the function of smoking, smoking place and smoking time. The magnitude of the influence of self-control on smoking intensity is 57.9% and the remaining 42.1% is influenced by other factors. The level of self-control in students at MTSS Manba'ul Huda Kalitekuk Kec. Gajah Kab. Demak is classified as moderate (83.6%) Keyword: Smoking behavior, Self-control